Psychometric Properties of the Interpersonal Behaviors Questionnaire in Sport in university athletes from Lima - Cáceres, Sebastián (2021)
The aim of this research was to investigate the psychometric properties of the Interpersonal Behaviors Questionnaire in Sport adapted to Peru. Based on Self-Determination Theory, this questionnaire assess the perception of interpersonal behaviors that support or thwart the basic psychological needs of athletes (autonomy, competence, relatedness) by their coaches. 228 university athletes (Mage = 21.24; SD = 2.39) of both sexes participated in the study. The results of the confirmatory factor analyzes showed that a six-factor model obtained good fit index and adequate reliability. Correlational analyzes with variables: life satisfaction, positive and negative affect, satisfaction and frustration of basic psychological needs, and burnout showed satisfactory evidence of convergent and discriminant validity. Thus, it was concluded that the IBQD could be used in the university sports Peruvian context to assess the perception of interpersonal behaviors displayed by its trainers.